Necessities and luxuries in satisfying single lives. (March 2023) - Park, Yoobin; MacDonald, Geoff
Despite the growing interest in single (unpartnered) individuals' well-being, there is a lack of descriptive research providing a comprehensive understanding of what singles value in their lives. In this research, we adopted a budget allocation methodology to examine what domains are prioritized in single individuals' construal of a satisfying single life. We recruited two samples of participants, one primarily consisting of singles from Europe and America ( N = 851) and the other from Korea ( N = 1012). Across the two samples, we found that singles gave high priority to being mentally and physically healthy and having good family relationships. Only when those essentials were accounted for did single individuals turn significant attention to other life domains such as having good friendships, available romantic connections, and sexual opportunities. These findings have implications for understanding single individuals' life priorities and well-being and set the groundwork for further research on singlehood.